AN ANALYSIS OF COMMUNICATION STRATEGIES IN SPEAKING - Widiastuti, Ni Luh Anis; Tantra, Dewa Komang; Padmadewi, Ni Nyoman (Universitas Pendidikan Ganesha, 2021)
The scientific approach in the learning process. There are still some problems in applying the five main procedures of the Scientific Approach in learning activities. Activities must be by the stages of the Scientific Approach. This study aimed to analyze the type of communication between junior high school students during speaking class in junior high school who applied the 2013 curriculum. This study was qualitative using a qualitative design. Data collection is done through direct observation. In data collection, the study used a cellular recorder. In addition, observation sheets were also used to obtain data. Data were taken descriptively. The results of this study indicate that the teacher applies a 15-dimensional Communication Strategy, namely Literal Translation, Code Switching, Pantomime, Message Reduction, Message Substitution, Repetition, Use of Fillers, Verb Strategy Maker, Self Accuracy, Response, Asking Clarification, Asking for Confirmation, Asking for Help, Repetition Request, and Comprehension Comprehension. Of the 15 strategies applied, Response has the highest proportion of events around 23.72%. Meanwhile, students only use seven dimensions of Communication Strategy. Those are Self-Improvement, Self-Improvement, Pantomime, Code Switching, Use of Fillers, Expressing Disappointment, Explanation of Repetition, Pantomime has the highest occurrence. That is a 34.21% occurrence.Â